Legal Basis of Sharia, Terms of Payment Period, and Permissible Goods in Borrowing and Lending - Bagas Wicaksono Boujesta; Hudallah (Ushul Al-Hukm: Jurnal Syariah dan Hukum Islam, 2025)
Lending and borrowing transactions are an important part of the economic life of Muslims, which includes various aspects such as borrowing money, goods or services with certain conditions. However, in Islam, these transactions must comply with the principles established by the Shari'a so as not to violate religious law. In this context, it is important to understand the legal basis that forms the basis of lending and borrowing transactions according to Islamic teachings, including the payment terms that must be adhered to, the types of goods that are permitted to be borrowed or lent, as well as the rules that regulate each loan so that avoid the elements of usury. With a deep understanding of the legal basis and principles related to lending and borrowing transactions in Islam, it is hoped that Muslims can carry out their economic activities in a more obedient manner to religious teachings and avoid practices that are contrary to the Shari'a. Therefore, research and studies on this topic are very relevant and useful for all parties who want to understand more deeply about Islamic law in an economic context.